2015
DOI: 10.1002/jat.3140
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of the hippocampal dentate gyrus in an adult toxicity study captures a variety of neurodevelopmental dysfunctions in rat models of hypothyroidism

Abstract: We previously found that developmental hypothyroidism changed the expression of genes in the rat hippocampal dentate gyrus, a brain region where adult neurogenesis is known to occur. In the present study, we performed brain region-specific global gene expression profiling in an adult rat hypothyroidism model to see if it reflected the developmental neurotoxicity we saw in the developmental hypothyroidism model. Starting when male rats were 5 weeks old, we administered 6-propyl-2-thiouracil at a doses of 0, 0.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Then, rats were randomly divided into three groups ( n = 10 per group), the control (C), low dose (L), and high dose (H) groups, and received normal saline, 0.001%, and 0.1% PTU by intragastric gavage for 60 days, respectively. 15,28 Their body weights (BWs) were measured once every 3 days.…”
Section: Methodsmentioning
confidence: 99%
“…Then, rats were randomly divided into three groups ( n = 10 per group), the control (C), low dose (L), and high dose (H) groups, and received normal saline, 0.001%, and 0.1% PTU by intragastric gavage for 60 days, respectively. 15,28 Their body weights (BWs) were measured once every 3 days.…”
Section: Methodsmentioning
confidence: 99%
“…Then, the experimental rats were randomly divided into control (C), low dose (L) and high dose (H) groups, and were administered with 1 mL per 100 g BW per day normal saline, 0.001% and 0.1% PTU, respectively, by intragastrical gavage for 60 days. 7,36 The body weights of the rats were measured every three days.…”
Section: Animals and Treatmentmentioning
confidence: 99%
“…In agreement with this hypothesis, we demonstrated earlier that different patterns of disruption of hippocampal neurogenesis occur between developmental and postpubertal exposure of VPA (Watanabe et al, 2019; Watanabe, Murakami, et al, 2017). We also previously reported that the pattern of disruption of hippocampal neurogenesis by developmental neurotoxicants such as PTU and MNU may be different between developmental and postpubertal exposure; this is in contrast to the similar patterns of disruption that occur after developmental and postpubertal exposure to adult‐type neurotoxicants, such as cuprizone and glycidol (Abe et al, 2015, 2016; Akane, Shiraki, et al, 2013, 2014; Shiraki et al, 2016; Watanabe, Nakajima, et al, 2017). In the present study, the finding of no or very low similarity in the gene expression profiles of the four brain regions between developmental and postpubertal exposure to VPA supported our hypothesis.…”
Section: Discussionmentioning
confidence: 92%
“…These results suggest that it is possible to predict adult‐type neurotoxicity by examining cellular responses in hippocampal adult neurogenesis and its regulatory system in a 28‐day repeated toxicity test using rats. In contrast, developmental neurotoxicants, such as 6‐propyl‐2‐thiouracil (PTU) and N ‐methyl‐ N ‐nitrosourea (MNU), have been reported to affect the granule cell lineage and γ‐aminobutyric acid (GABA)‐ergic interneuron subpopulations differently between developmental and postpubertal exposure (Shiraki et al, 2016; Watanabe, Nakajima, et al, 2017). Of note, the effects of developmental neurotoxicants may also be detected after postpubertal exposure if disruption of hippocampal neurogenesis is confirmed.…”
Section: Introductionmentioning
confidence: 99%